Comparison of SKA1 serum levels in oral potentially malignant disorders and oral squamous cell carcinoma - Khan, Samreen; Muhammad Mohiuddin Alamgir; Uzma Bukhari; Muhammad Shuja Farrukh (Journal of the Pakistan Medical Association, 2025)
Objective: To compare serum levels of spindle and kinetochore-associated complex subunit 1 in oral potentially malignant disorders and oral squamous cell carcinoma. Method: The analytical, cross-sectional study was conducted from July 2022 to April 2023 at the Department of Otolaryngology of Dr Ruth Pfau Civil Hospital, Karachi, Dr Ishrat-ul-Ebad Khan Institute of Oral Health Sciences, Karachi, and the histopathological section of the Dow Diagnostic Reference and Research Laboratory at the Dow University of Health Sciences, Karachi, and comprised serum samples of patients with oral squamous cell carcinoma and oral potentially malignant disorder. The concentrations of serum spindle and kinetochore-associated complex subunit 1 were determined using the enzyme-linked immunosorbent assay method. Data was analysed using SPSS 21. Results: Of the 90 patients with age ranging 30-90 years, 45(50%) had oral squamous cell carcinoma; 34(75.6%) males and 11(24.4%) females. There were 45(50%) patients with oral potentially malignant disorders; 35(77.8%) males and 10(22.2%) females (p>0.05). The median serum spindle and kinetochore associated complex subunit 1 levels were significantly elevated in patients with oral squamous cell carcinoma compared to those with oral potentially malignant disorders (p<0.05). Conclusion: Spindle and kinetochore-associated complex subunit 1 could be a promising non-invasive serum marker for the early detection of malignant transformation in oral potentially malignant disorders and for prediction of prognosis in oral squamous cell carcinoma cases. Key Words: Spindle and kinetochore-associated complex subunit 1, Oral squamous cell carcinoma, Oral potentially malignant disorder.